Komitmen untuk Hidup Sesuai Identitas Diri Yang Baru dalam Kristus - Epafras Mujono; Anti Uki Nusantari (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
This research as a whole consists of two parts: The first part is a descriptive study of the literature, and the second part is the result of field research. The discussion of identity in Christ is focused on the Book of Philippians. This research is motivated by the fact at the place of study that there are young Christians who are less committed to living in their identity in Christ. This is shown by some facts such as, when youths to worship together in less youth worship, attendance in worship is relatively low. Some young Christians easily do not worship because they are too busy with study / work assignments, why there are events at study sites or jobs, the reasons for relatives or friends coming from out of town, there are even reasonable reasons for watching football broadcast on television or with not easy to worship just because of rain and so on.